Analysis of Barriers to Sustainable Supply Chain Implementation Using DEMATEL and ISM Integration - Kuswara, Ramadana Esa; Ernawati, Dira; Nugraha, Isna (Newinera Publisher, 2024)
CV. XYZ found barriers that could hinder the implementation of a sustainable supply chain in the company. However, the company does not have a resolution method for determining the priority barriers that most influence the implementation. The aim of this research is to determine the barriers that influence the implementation of a sustainable supply chain. Settlement is carried out using the DEMATEL-ISM method. The research results show that the most influential barriers are lack of regulation and guidance from the government (A9) and high initial investment (A1). Because in the DEMATEL-ISM integration, these two factors were found to be located at the lowest level, which is the level with the most influential barriers, which are the main drivers. As a result, companies need to prioritize lack of regulation and guidance from the government and high initial investment as a basis for evaluation and improvement in implementing sustainable supply chains.